2021
DOI: 10.3390/antiox10060839
|View full text |Cite
|
Sign up to set email alerts
|

ROS Defense Systems and Terminal Oxidases in Bacteria

Abstract: Reactive oxygen species (ROS) comprise the superoxide anion (O2·−), hydrogen peroxide (H2O2), hydroxyl radical (·OH), and singlet oxygen (1O2). ROS can damage a variety of macromolecules, including DNA, RNA, proteins, and lipids, and compromise cell viability. To prevent or reduce ROS-induced oxidative stress, bacteria utilize different ROS defense mechanisms, of which ROS scavenging enzymes, such as superoxide dismutases, catalases, and peroxidases, are the best characterized. Recently, evidence has been accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 132 publications
(173 reference statements)
0
57
0
Order By: Relevance
“…It is suggested that H 2 S prevents oxidative DNA damage in bacteria via the following cytoprotective mechanisms: (i) direct reduction of H 2 O 2 into H 2 O; (ii) depletion of Fe 2+ , a catalyst of the Fenton reaction; (iii) transient depletion of free cysteine, a reducing agent that fuels the Fenton reaction; and (iv) stimulation of the activities of superoxide dismutase (SOD) and catalase [ 15 ]. The latter two enzymes are the well-known ROS scavenging systems [ 16 ]. It should be noted, however, that Shatalin et al [ 15 ] did not suggest a mechanism for the depletion of Fe 2+ and free cysteine by H 2 S.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that H 2 S prevents oxidative DNA damage in bacteria via the following cytoprotective mechanisms: (i) direct reduction of H 2 O 2 into H 2 O; (ii) depletion of Fe 2+ , a catalyst of the Fenton reaction; (iii) transient depletion of free cysteine, a reducing agent that fuels the Fenton reaction; and (iv) stimulation of the activities of superoxide dismutase (SOD) and catalase [ 15 ]. The latter two enzymes are the well-known ROS scavenging systems [ 16 ]. It should be noted, however, that Shatalin et al [ 15 ] did not suggest a mechanism for the depletion of Fe 2+ and free cysteine by H 2 S.…”
Section: Introductionmentioning
confidence: 99%
“…HCOs catalyze the transfer of electrons from quinols or cytochromes to oxygen with the formation of water coupled to the generation of proton motive force [ 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In contrast to bd -type oxidases, HCOs generate the proton motive force not only by the transfer of electrons and protons to the catalytic center from different sides of the membrane but also due to the unique ability for redox-coupled directed proton pumping through the membrane [ 23 ].…”
Section: Introduction: General Properties Of Terminal Respiratory Oxidasesmentioning
confidence: 99%
“…Members of the other two families use cytochrome c and possibly another electron donor different than quinol [ 4 ]. Notwithstanding, to date all the biochemically characterized bd -type cytochromes appeared to be quinol oxidases [ 14 , 78 , 79 , 80 ]. Further research is required to obtain and characterize a bd enzyme that would use an electron donor other than quinol.…”
Section: Introduction: General Properties Of Terminal Respiratory Oxidasesmentioning
confidence: 99%
See 2 more Smart Citations